2021
DOI: 10.1021/acschembio.1c00422
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Recognition of a Monoclonal Antibody Raised against a Synthetic Glycerol Phosphate Based Teichoic Acid

Abstract: Glycerol phosphate (GroP)-based teichoic acids (TAs) are antigenic cell-wall components found in both enterococcus and staphylococcus species. Their immunogenicity has been explored using both native and synthetic structures, but no details have yet been reported on the structural basis of their interaction with antibodies. This work represents the first case study in which a monoclonal antibody, generated against a synthetic TA, was developed and employed for molecular-level binding analysis using TA microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…We recently developed a TA microarray to evaluate antibody binding to a large set of poly­(glycerolphosphate) (GroP)-based lipoteichoic acid (LTA) oligomers . We have applied this TA microarray to map the recognition of different mAbs as well as polyclonal sera. ,, To start our binding studies of the mAbs 4497 and 4461, we here generated an array presenting both WTA and LTA fragments (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed a TA microarray to evaluate antibody binding to a large set of poly­(glycerolphosphate) (GroP)-based lipoteichoic acid (LTA) oligomers . We have applied this TA microarray to map the recognition of different mAbs as well as polyclonal sera. ,, To start our binding studies of the mAbs 4497 and 4461, we here generated an array presenting both WTA and LTA fragments (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…18 We have applied this TA microarray to map the recognition of different mAbs as well as polyclonal sera. 15,19,20 To start our binding studies of the mAbs 4497 and 4461, we here generated an array presenting both WTA and LTA fragments (Figure 3).…”
Section: ■ Introductionmentioning
confidence: 99%
“…A recent study used microarrays comprised of various synthetic WTA glycans to identify the recognition motif of a mAb (WH7.01) generated by immunization of mice with WH7, a synthetic version of a GroP WTA hexamer. 151 Screening of WH7.01 with these WTA microarrays-in combination with ELISA, SPR analyses, and STD-NMR spectroscopy-found that this mAb recognized GroPbased WTA fragments but not similar RboP-containing WTAs. 151 This indicates that the GroP moiety is the main recognition element for this anti-WTA mAb.…”
Section: Antibodies To Bacterial Glycansmentioning
confidence: 99%
“…151 Screening of WH7.01 with these WTA microarrays-in combination with ELISA, SPR analyses, and STD-NMR spectroscopy-found that this mAb recognized GroPbased WTA fragments but not similar RboP-containing WTAs. 151 This indicates that the GroP moiety is the main recognition element for this anti-WTA mAb. 151 Glycan microarrays have also been used to assess antibody recognition of the capsular polysaccharides (CPSs) of the Grampositive bacteria S. pneumoniae [152][153][154][155] Clostridium difficile, and Bacillus anthracis.…”
Section: Antibodies To Bacterial Glycansmentioning
confidence: 99%
“…The serum raised against the native LTA bound the opposite stereochemistry GroP better as it better resembles how LTA is anchored in the bacterial cell wall. A follow-up study elucidated the interactions of a mAb generated against (52) and a library of LTA structures through a combination of glycan array, ELISA, SPR-analyses, and STD-NMR spectroscopy to show that the number of GroP residues was important for affinity of the mAb and that binding was indirectly effected by the presence of the glucose residue . This study confirmed the importance of the backbone chirality.…”
Section: Emerging Amr Targetsmentioning
confidence: 99%